2019
DOI: 10.3390/nu11020298
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Score of Predisposition to Low-Grade Inflammation Associated with Obesity May Contribute to Discern Population at Risk for Metabolic Syndrome

Abstract: Omega-3 rich diets have been shown to improve inflammatory status. However, in an ex vivo system of human blood cells, the efficacy of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) modulating lipid metabolism and cytokine response is attenuated in overweight subjects and shows high inter-individual variability. This suggests that obesity may be exerting a synergistic effect with genetic background disturbing the anti-inflammatory potential of omega-3 long-chain polyunsaturated fatty acids (PUFA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 91 publications
(95 reference statements)
0
22
0
2
Order By: Relevance
“…In this regard, Polyunsaturated Fatty Acids (PUFA) are a bio-active group of compounds present in fish oils, algae, and other food sources [ 153 ]. Despite the fact that genetic and anthropometric factors should be taken into account to consider their benefits, omega-3 PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) show anti-inflammatory proprieties [ 154 , 155 ] and a combined adequate intake of 250 mg/day is considered necessary for the maintenance of general cardiovascular health [ 156 ]. In this context, the potential benefits (and risks) of omega-3 PUFA supplementation to COVID-19 patients were recently reviewed [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Polyunsaturated Fatty Acids (PUFA) are a bio-active group of compounds present in fish oils, algae, and other food sources [ 153 ]. Despite the fact that genetic and anthropometric factors should be taken into account to consider their benefits, omega-3 PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) show anti-inflammatory proprieties [ 154 , 155 ] and a combined adequate intake of 250 mg/day is considered necessary for the maintenance of general cardiovascular health [ 156 ]. In this context, the potential benefits (and risks) of omega-3 PUFA supplementation to COVID-19 patients were recently reviewed [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of genomic DNA was carried out using the commercial kit High Pure PCR template Preparation Kit (Roche, Basel, Switzerland). Genotyping was performed by qPCR (LightCycler ® 480 FastStart DNA, Roche, Basel, Switzerland), FastStart master mix (Roche, Basel, Switzerland), and specific-SNP (Tib Molbiol, Berlin, Germany) following the conditions described elsewhere [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Obesity constitutes one of the largest public health issues in the world and is associated with widespread comorbidities, including insulin resistance, hypertension, cardiovascular disease, stroke, sleep apnea, cancer, chronic inflammation, and mortality (6)(7)(8)(9). Though inflammation in obesity is multifaceted, recent attention has turned to genetic contributions of underlying inflammatory mechanisms (10,11). In particular, studies have shown that obesity induces cytosolic mitochondrial DNA release, which triggers activation of STING (stimulator of interferon genes; refs.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%